Treponema denticola Promotes OSCC Development via the TGF-β Signaling Pathway. (June 2022) - Peng, R.T.; Sun, Y.; Zhou, X.D.; Liu, S.Y.; Han, Q.; Cheng, L.; Peng, X.
Numerous studies have demonstrated an association between periodontitis and oral squamous cell carcinoma (OSCC), and periodontal pathogens such as Treponema denticola are implicated in the pathogenesis of OSCC. Previous studies have mainly focused on T. denticola surface proteins—for example, chymotrypsin-like proteinase, which was detected in the majority of orodigestive tumor tissues. T. denticola may influence the development of OSCC. Nevertheless, the potential direct regulatory mechanism of T. denticola in OSCC is still unclear. Therefore, this study aimed to explore the direct effect of T. denticola on OSCC cell proliferation and elucidate potential mechanisms of T. denticola in contributing to cell proliferation. A series of in vitro experiments (e.g., CCK-8, EdU, flow cytometry) were performed to explore the effect of T. denticola on cell proliferation, cell cycle, and apoptosis. Mice experiments were performed to explore the effect of T. denticola on tumor growth. Whole mRNA transcriptome sequencing and quantitative real-time polymerase chain reaction were performed to explore the intracellular signaling pathway. Our study found that T. denticola could invade Cal-27 cells and directly promote cell proliferation, regulate the cell cycle, and inhibit apoptosis. T. denticola could also promote the growth of OSCC tumors in mice, and it upregulated Ki67 expression. Regarding the mechanism, T. denticola could promote the development of OSCC by activating the TGF-β pathway. In conclusion, T. denticola could promote OSCC cell proliferation directly, and the mechanism was associated with intracellular TGF-β pathway activation.